2022
DOI: 10.1371/journal.pone.0270764
|View full text |Cite
|
Sign up to set email alerts
|

Incidental detection of paranasal sinuses abnormalities on CT imaging of the head in Saudi adult population

Abstract: The paranasal sinuses are hollowed, air-filled cavities surrounding the nasal cavity. Many pathological processes affect the sinuses, but inflammatory conditions are the commonest, even in asymptomatic patients who undergo head imaging for other indications showing one or more abnormalities of the sinuses. Our research aims to determine the prevalence of incidental paranasal sinuses abnormalities seen among patients who undergo head CT scanning. In addition, it provides baseline information for further investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Previous studies have sought to develop minimal radiographic criteria for CRS as greater than the extent of incidental radiographic findings in individuals without sinonasal symptoms and no history of CRS. Paranasal sinus mucosal thickening has been found incidentally in asymptomatic individuals 11‐13 . Some of these findings may be transient and spurious but it is also known that radiographic evidence of sinonasal inflammation may occur and persist long after the resolution of an upper respiratory tract infection 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have sought to develop minimal radiographic criteria for CRS as greater than the extent of incidental radiographic findings in individuals without sinonasal symptoms and no history of CRS. Paranasal sinus mucosal thickening has been found incidentally in asymptomatic individuals 11‐13 . Some of these findings may be transient and spurious but it is also known that radiographic evidence of sinonasal inflammation may occur and persist long after the resolution of an upper respiratory tract infection 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Paranasal sinus mucosal thickening has been found incidentally in asymptomatic individuals. [11][12][13] Some of these findings may be transient and spurious but it is also known that radiographic evidence of sinonasal inflammation may occur and persist long after the resolution of an upper respiratory tract infection. 14 One previous study has shown that the degree of mucosal thickening in each of the paranasal sinuses of CRS patients is significantly greater than in control patients, although with considerable overlap and many CRS patients do not have opacification or mucosal thickening in every sinus.…”
Section: Discussionmentioning
confidence: 99%